Parental Communication Strategies in Sustaining the Social Relationships of Dahlia Boarding School Students, Medan Tembung District, Medan City - Aini, Fatima; MG, Nashrillah (UIN Fatmawati Sukarno Bengkulu, 2024)
This study seeks to examine the communication strategies employed by parents to sustain the social interactions of children residing at the Dahlia Boarding House in the Medan Tembung District of Medan City. This study employs a qualitative descriptive methodology, utilizing data collection techniques such as in-depth interviews, direct observation, and literature reviews from pertinent publications. The research findings indicate the existence of three primary communication types employed by parents: authoritarian, authoritative, and permissive. Authoritarian communication patterns are defined by rigid control and explicit directives from parents, whereas authoritative communication patterns integrate oversight with a nurturing, conversational method. Conversely, permissive communication patterns afford students increased autonomy in decision-making, even with limited oversight. The three communication patterns significantly affect student behavior and relationships; thus, selecting the appropriate pattern is essential for fostering a harmonious relationship between parents and children residing in boarding houses.